SINERGI SHARI‘AH, TARIQAH DAN HAQIQAH - Musyafa’, Muhammad (Mahad Aly Al Fithrah Press, 2019)
Shari’ah is knowledge, thariqah is applying the knowledge and haqiqah is the result of knowledge application that is reaching the mercies of Allah. Haqiqah is devided into three part. First, easy to do good action (Amal Shalih).Second, al-takhalli ‘an radzail wa al-tahalli bil mahamid. Third, disclosure of someone self separation with everything he believe in, as if he sees and witnesses directly. Shariah is like a ship it has function as transpotation medium to reach the destination, while thariqah is like the ocean, it is the place to reach the destination, and haqiqah is like the prisious gemstone. Every application of shari’ah without implementing Tasawuf, thariqah will lead to be fasik and will be empty from the heart beahviour as like sincerity. Every tariqah gainst the shariah will lead to be kufur. Every haqiqah which unable to be corrected by quran and sunnah will lead to deviation, liberalis and zanaqiah. Takamul al-shari‘ah wa al-tariqah wa al-haqiqah build a perfect soul and personality.